2011
DOI: 10.1007/s10803-011-1431-6
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Oscillatory Activity in Autism Spectrum Disorders

Abstract: Neural oscillatory anomalies in autism spectrum disorders (ASD) suggest an excitatory/inhibitory imbalance; however, the nature and clinical relevance of these anomalies are unclear. Whole-cortex magnetoencephalography data were collected while 50 children (27 with ASD, 23 controls) underwent an eyes-closed resting-state exam. A Fast Fourier Transform was applied and oscillatory activity examined from 1 to 120 Hz at 15 regional sources. Associations between oscillatory anomalies and symptom severity were probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
175
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(209 citation statements)
references
References 55 publications
28
175
1
Order By: Relevance
“…Our findings are consistent with previous experimental findings in a MEG and EEG studies performed in a non-clinical setting [5,7]. Routine EEG is a commonly available investigation and can be used without sedation across a wider range of age groups and in children with developmental disabilities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous experimental findings in a MEG and EEG studies performed in a non-clinical setting [5,7]. Routine EEG is a commonly available investigation and can be used without sedation across a wider range of age groups and in children with developmental disabilities.…”
Section: Discussionsupporting
confidence: 92%
“…One EEG study has reported an increase in gamma activity during an eyes-open sustained attention task in children with ASD [5], while another found evidence for localized decreased gamma activity using the same EEG paradigm [6]. A recent MEG study found elevated 20-120 Hz activity during an eyes-closed condition predominantly in posterior brain regions [7].…”
Section: Introductionmentioning
confidence: 99%
“…The baseline decreased resting state a power was consistent with other EEG studies in ASD. 25,26 Moreover, a role for a frequency band oscillations has been shown in specific cognitive mechanisms. 27 The increase in the a frequency power after treatment may be an underlying mechanism of patient's improvement in cognition and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A recent magnetoencephalography study comparing brain activity in individuals with autism with that in age-matched controls indicated that those with autism have increased resting-state power of multiple frequency bands. 21 Alpha and delta powers were elevated in frontoparietal channels, and increases in the latter have been associated with gray-white matter disconnection. 40 In the study by Cornew and colleagues, 21 broadband gamma power was increased in posterior channels.…”
Section: Electrophysiological Disturbancesmentioning
confidence: 99%
“…21 Alpha and delta powers were elevated in frontoparietal channels, and increases in the latter have been associated with gray-white matter disconnection. 40 In the study by Cornew and colleagues, 21 broadband gamma power was increased in posterior channels. Stimulus-induced electrophysiological changes in autism are not well studied, but EEG studies of pure-tone auditory stimuli in individuals with autism have shown increased event-related potential latency along with deficits in phase-locked gammaband power in the superior temporal gyrus.…”
Section: Electrophysiological Disturbancesmentioning
confidence: 99%